2023
DOI: 10.1111/pce.14610
|View full text |Cite
|
Sign up to set email alerts
|

The CsHSFA‐CsJAZ6 module‐mediated high temperature regulates flavonoid metabolism in Camellia sinensis

Abstract: High temperatures (HTs) seriously affect the yield and quality of tea. Catechins, derived from the flavonoid pathway, are characteristic compounds that contribute to the flavour of tea leaves. In this study, we first showed that the flavonoid content of tea leaves was significantly reduced under HT conditions via metabolic profiles; and then demonstrated that two transcription factors, CsHSFA1b and CsHSFA2 were activated by HT and negatively regulate flavonoid biosynthesis during HT treatment. Jasmonate (JA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…CsJAZ6 could represses catechin biosynthesis by directly interacting with CsEGL3 and CsTTG1, and the silencing of CsJAZ6 in tea leaves causes the upregulation of almost all genes involved in flavonoid biosynthesis and a decrease in catechin content. These findings suggest that JA serves as a central regulator mediating the regulatory effect of high temperature on the flavonoid synthesis pathway [76].…”
Section: Ja Regulation In Abiotic Stress Processesmentioning
confidence: 79%
“…CsJAZ6 could represses catechin biosynthesis by directly interacting with CsEGL3 and CsTTG1, and the silencing of CsJAZ6 in tea leaves causes the upregulation of almost all genes involved in flavonoid biosynthesis and a decrease in catechin content. These findings suggest that JA serves as a central regulator mediating the regulatory effect of high temperature on the flavonoid synthesis pathway [76].…”
Section: Ja Regulation In Abiotic Stress Processesmentioning
confidence: 79%
“…In Arabidopsis , JAZ proteins weakened the transcriptional activity of the MBW complex by interacting with bHLH and MYB TFs, repressing JA-induced anthocyanin accumulation [ 33 , 69 ]. In tea plant, CsJAZ6 interacted with the MBW components CsEGL3 and CsTTG1, and the induction of JA weakened the inhibitory effect of CsJAZ6 on CsEGL3 and CsTTG1, leading to an increase in the biosynthesis of catechins under heat stress [ 70 ]. In our study, we found 13 ScJAZ genes in the jojoba genome, five of which were selected for analysis of their interactions with bHLH TF—ScTT8.…”
Section: Discussionmentioning
confidence: 99%
“…Research on tea plants has often focused attention towards the growing period, while foliar nitrogen application during the winter dormancy of tea plants improves the nitrogen content of mature leaves with the quality and yield of spring tea, while fertilizer dosage can be reduced [ 177 ]. The interaction between hormones and metabolites within the tea plants also influenced quality, as the expression of CsJAZ6 in tea plants inhibited the JA pathway, which regulated most secondary metabolites, notably catechins, and the interaction between CsJAZ6 and catechin biosynthesis regulators negatively regulated catechin accumulation [ 178 ]. Apart from endogenous hormones, endogenous hormone signaling factors could also mediate the synthetic pathways of caffeine, EGCG and theanine to respond to temperature and improve the quality of tea leaves [ 179 ].…”
Section: Major Directions and Measures For Tea Plants Breedingmentioning
confidence: 99%